France, M. H., Rodríguez, M. d. C., & Hett, G. G. (2021). Diversity, culture, and counselling: A Canadian perspective (3rd ed.). Brush Education. ISBN: 978-1- 55059-875-9, xi + 610 pp. - Tong, Caryn (Canadian Journal of Counselling and Psychotherapy, 2025)
Divided into three sections, this edited volume offers a comprehensive view of the foundational issues, cultural communities, and practical approaches involved in working with a diverse clientele. Contributions to this book include a wide overview of the issues that arise when working with a culturally diverse clientele and a consideration of a broad range of issues with diversity, including vulnerable populations. Chapters address issues of cultural identity development and specific populations, discussing relevant historical contexts as well as practical points that inform best practices. This book is both informative and practical, serving as both a primer and as a succinct source of information. The specific focus on cross-cultural competency versus the more commonly used term of cultural competency highlights the importance of continued development of competency for practitioners.